1998
DOI: 10.1242/jcs.111.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Cells from ercc1-deficient mice show increased genome instability and a reduced frequency of s-phase-dependent illegitimate chromosome exchange but a normal frequency of homologous recombination

Abstract: The ERCC1 protein is essential for nucleotide excision repair in mammalian cells and is also believed to be involved in mitotic recombination. ERCC1-deficient mice, with their extreme runting and polyploid hepatocyte nuclei, have a phenotype that is more reminiscent of a cell cycle arrest/premature ageing disorder than the classic DNA repair deficiency disease, xeroderma pigmentosum. To understand the role of ERCC1 and the link between ERCC1-deficiency and cell cycle arrest, we have studied primary and immorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…These results suggest that ERCC1 is not generally required for targeted homologous recombination and demonstrate that the short terminal non‐homologies blocking both arms of targeting homology in the pAG6 vector can be effectively removed by ERCC1 ‐independent pathways. While our results appear to support the conclusion of Melton et al . (1998) that ERCC1 is not required for the general recombination pathways involved in gene targeting, they are difficult to reconcile with findings by Schiestl and Prakash (1988, 1990) that in yeast, RAD1 or RAD10 knockouts markedly reduce the frequencies of targeted integration by linearized insertion vectors with no terminal non‐homology.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results suggest that ERCC1 is not generally required for targeted homologous recombination and demonstrate that the short terminal non‐homologies blocking both arms of targeting homology in the pAG6 vector can be effectively removed by ERCC1 ‐independent pathways. While our results appear to support the conclusion of Melton et al . (1998) that ERCC1 is not required for the general recombination pathways involved in gene targeting, they are difficult to reconcile with findings by Schiestl and Prakash (1988, 1990) that in yeast, RAD1 or RAD10 knockouts markedly reduce the frequencies of targeted integration by linearized insertion vectors with no terminal non‐homology.…”
Section: Discussionsupporting
confidence: 88%
“…In S.cerevisiae , the Rad1/Rad10 endonuclease appears to be required not only for removal of long, 3′‐ended, non‐homologous single‐stranded tails from SSA recombination intermediates during DSB‐induced recombination between direct repeats, but also for the removal of such blocking non‐homologies from the 3′‐OH ends of invading homologous strands in other pathways of DSB‐induced homologous recombination (Fishman‐Lobell and Haber, 1992; Ivanov and Haber, 1995; Prado and Aquilera, 1995; Saparbaev et al ., 1996; Sugawara et al ., 1997; Paques and Haber, 1997, 1999; Colaiacovo et al ., 1999). Although two previous studies in mammalian cells failed to demonstrate a general effect of ERCC1 deficiency on either the rate of spontaneous intrachromosomal homologous recombination between direct repeats (Sargent et al ., 1997) or the overall frequency of gene targeting (Melton et al ., 1998), neither study was designed to investigate the role of ERCC1 in recombination events that would specifically require the removal of terminal non‐homologies. To examine this most likely role of ERCC1 directly, we conducted gene targeting experiments employing two insertion‐type vectors (pAG6 and pAG6ins0.9), in which both arms of APRT targeting homology were blocked by very short or substantially longer terminal non‐homologies flanking each side of a DSB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the importance of MOC-IV may change during pharmacological treatment. Several studies have shown that chronic treatment with cisplatin could induce the expression of many MOC-IV genes. Thus, in the present study HepG2 cells were found to be very sensitive to treatment with cisplatin, which induced a marked and generalized increase in the expression of the genes included in MOC-IV.…”
Section: Discussionsupporting
confidence: 52%